Antimicrobial Susceptibility Pattern of E. Coli in Patients with Urinary Tract Infection at a Tertiary Care Hospital, Rawalpindi - Irum Anwar, Shireen Rafiq, Kiran Ahmad, Mutshera Ul Mubeen, Ayesha Mudassar, Muhammad Kamran, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Urinary tract infections caused by bacteria are the most prevalent type of hospital-acquired infection. They are also responsible for the greatest number of patient fatalities, lengths of hospital stays, and overall costs associated with medical care. Even though Escherichia coli is the bacteria that is found the most frequently, several studies have found different levels of prevalence for it. The current dilemma with antibiotic resistance is being caused, in large part, by the inappropriate and excessive use of antibiotics. Methodology: Laboratory records were searched in order to obtain information regarding the organisms that were isolated from urine samples as well as the pattern of antibiotic susceptibility. The urine samples that were obtained were processed according to the normal procedures, and a Kirby-Bauer Disk Diffusion test was used to determine the antibiotic susceptibility of the bacteria. Results: E. coli was found to be the most frequent causative agent of UTI (40.6%) followed by candida spp. (28%), Enterococcus spp (10.6%), Klebsiella spp (9.8%), Staphylococcus aures (1.58%) and Acinatobacter spp (1.97%). E. coli showed variable antimicrobial resistance to various antibiotics such as AMP (95.6%) followed by CRO (91.5%), CAZ (86.5%), CTX (82.09%), and MXF (80.8%) while most sensitive antibiotic was fosfomycin (93.2%) followed by sulzone (83.5%), imepinem (78.1%) and amikacin (77.1%). Keywords: Pathogens, susceptibility pattern, urinary tract infection